PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MATEMATIKA BERBASIS ETNOMATEMATIKA DALAM MENUNJANG PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Rita Ningsih; Wardi Syafmen; Novferma (Universitas Insan Budi Utomo, 2026)
This study aims to develop a learning medium in the form of an ethnomathematics-based mathematics comic to support differentiated instruction and increase students’ interest in learning. This research is a type of development study using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study include Mathematics Education lecturers at the University of Jambi as expert team, a mathematics teacher in the individual trial, 9 students of class IX B in the small group trial, and all students of class IX A at SMP Negeri 1 Kota Jambi in the field trial. The results of the study indicate that the ethnomathematics-based mathematics comic learning media meets the criteria of being valid, practical, and effective. The validity of the mathematics comic is based on the results of material and design validation questionnaires, showing percentages of 84% for the material aspect and 86.8% for the design aspect, both categorized as very valid. The level of practicality is determined from practicality questionnaires completed by teachers and students, with percentages of 92.04% and 92.7%, respectively, which fall into the very practical category. The effectiveness level of the mathematics comic, based on students’ learning interest questionnaires analyzed using the N-Gain score, shows a percentage of 64.88%, categorized as moderately effective. Therefore, the ethnomathematics-based mathematics comic learning media is suitable for use in the learning process as it meets the criteria of being valid, practical, and effective.